Pengaruh Kompetensi Dan Kemampuan Penggunaan Teknologi Terhadap Peningkatan Profesionalisme Guru (Studi Kasus SMK Budi Mulia Kotobaru) - Mutiara Pratiwi; Ida Nirwana; Rasidah Nasrah (Journal of Management and Creative Business, 2023)
This research was conducted at SMK Budi Mulia Kotobaru. The population in this study were all 33 teachers in Budi Mulia Kotobaru Vocational School, the sampling technique in this study was total sampling, where the number of samples was the same as the population. So the sample in this study were 33 people. The type of data used in this research is quantitative. Data collection technique is done by distributing questionnaires. This study aims to analyze the influence of competence and ability to use technology to increase the professionalism of teachers at Budi Mulia Kotobaru Vocational School. The sample in this study were 33 respondents who teach at SMK Budi Mulia Kotobaru. Based on the results of the analysis that has been carried out, it is obtained that Y = 4.133+ 0.582X1 + 0.339X2 + e and t-tests of 3.291 and 2.266, which means that the competence variable affects the professionalism of teachers at Budi Mulia Kotobaru Vocational School, the variable ability to use technology affects the professionalism of Budi Mulia Vocational School teachers. His Highness Kotobaru. Judging from the R Square value of 0.762, which means that competence and ability to use technology have an effect of 76.2% on increasing the professionalism of teachers at Budi Mulia Kotobaru Vocational School and 23.8% is influenced by other variables not examined in this study. From the analysis of the f-test the value of fcount is 47.899> ftable 3.30, which means that the competence and ability to use technology together affect the professionalism of teachers at Budi Mulia Kotobaru Vocational School.